Rethinking digital activism: The deconstruction, inclusion, and expansion of the activist body - Blaagaard, Bolette; Roslyng, Mette Marie (MedieKultur: Journal of media and communication research, 2022)
This article explores the following research question: How is political activism expressed in connective, affective, and embodied ways, and how do these modes result in a rearticulation of the body and central activist signifiers? While connective and affective dimensions of digital activism offer invaluable insights into the new forms of activist organisation, it remains underexplored how the activist body and the concepts of “human” and “rights” are discursively produced through digital expressions of activism. Therefore, drawing on a purposive selection of digital content, we produce a discursive analysis of three illustrative cases of digital activism relating to three major political contemporary issues: Black Lives Matter, #MeToo, and Extinction Rebellion. We argue that they each present different modes of embodied and discursively constructed signifiers of “human” and “rights”, which allows for a range of political aims and outcomes to be expressed through different degrees of antagonism calling, respectively, for deconstruction, inclusion, and expansion of the signifiers.